Rola Europejskiej Służby Działań Zewnętrznych w dyplomacji Unii Europejskiej .......... 151 - Bąk, Franciszek (Oblicza dyplomacji, 2025)
THE ROLE OF EUROPEAN EXTERNAL ACTION SERVICE IN EUROPEAN UNION’S DIPLOMACYThis article seeks to provide an in-depth exploration of the European External Action Service (EEAS) and its pivotal role in shaping the European Union’s diplomatic landscape. Through a comprehensive analysis, the study delves into the EEAS’s organizational structure, core mandates, and legal underpinnings, with the intent of demystifying the intricate mechanisms of EU diplomatic engagement. Utilizing a methodological approach that combines qualitative content analysis and institutional-legal examination, the research draws upon scholarly publications, official reports, and primary sources to construct a nuanced understanding of the EEAS’s strategic function in international relations.